PENOMORAN GANDA BERKAS REKAM MEDIS DI RSUD PASAR MINGGU - Rahmat,; Irda Sari, (Journal of Innovation Research and Knowledge, 2021)
Good medical record numbering is one of the keys to the success or goodness of medical record management of a health service, of course if supported by a good system. Quality human resources and good procedures or work procedures and adequate facilities or facilities. The purpose of medical record numbering is to distinguish the medical records of patients from each other. Duplication of numbering is generally caused by an incorrect identification process that causes a patient to obtain more than one medical record number. The purpose of this study is to find out the factors that affect the duplication of medical record numbering in Pasar Minggu Hospital. This study uses qualitative research type, conducted by interviewing medical record officers in registration. The population and research samples are medical records officers in the registration of 8 people. Data analysis uses interview guidelines, observation guidelines and primary data. Duplication of numbering at Pasar Minggu Hospital at the time of patient registration where patients get double numbers, and every day about 1-4 patients who get double numbers. Educational qualifications, knowledge, and experience are less thorough and less knowledgeable about medical record numbering systems. There is still duplication of medical record numbering and for officers it needs training and improving broad insights. It is expected that the hospital can pay attention to the registration officer in giving medical record numbering.